Serratus anterior or pectoralis minor: Which muscle has the upper hand during protraction exercises?. (April 2016) - Castelein, Birgit; Cagnie, Barbara; Parlevliet, Thierry; Cools, Ann
Abstract: Background: The Serratus Anterior (SA) has a critical role in stabilizing the scapula against the thorax. Research has linked shoulder and neck disorders to impairments in the SA activation. Exercises that target the SA are included in the rehabilitation of shoulder or neck pain and mostly include a protraction component. The Pectoralis Minor (PM) functions as a synergist of the SA. From the literature it is unclear to what extent PM is activated during SA exercises. Objectives: To determine the activity of SA and PM during different protraction exercises. Design: Controlled laboratory study. Method: 26 subjects performed 3 exercises: Modified Push-Up Plus (Wall Version), Modified Knee Push-Up Plus (Floor version) and Serratus Punch. Electromyographic (EMG) data was collected from the SA (surface) and PM (fine-wire EMG). Results: During the Serratus Punch the SA activity was significantly higher than the PM activity. During the Modified Push-Up Plus exercises (both Wall and Floor version), the SA and PM activity were comparable. The PM showed the highest activity during the Serratus Punch and the Modified Push-Up Plus (Floor), which was significantly higher than during the Modified Push-Up Plus (Wall). The SA showed the highest activity during the Serratus Punch, which was significantly higher than during the Modified Push-Up Plus (Floor) which was in turn significantly higher than the activity during the Modified Push-Up Plus (Wall). Conclusions: All exercises activated the PM between 15 and 29% Maximum Voluntary Isometric Contraction and the SA between 15 and 43%. The Modified Push-Up Plus exercise against the wall and the floor activated the SA and PM to a similar degree. When maximum activation of the SA with minimal activation of the PM is desired in healthy subjects, the "Serratus punch" seems to be the optimal exercise. Highlights: All exercises activated the Pm between 15 and 29% MVIC. The Modified Push-Up Plus (Wall and Floor) activated SA and Pm to a similar degree. The Serratus punch seems optimal in healthy subjects when maximum SA with minimal Pm activation is desired.